The Effect of Subject Matter Analysis (SMA) on Knowledge in the face of the Out of Hospital Cardiac Arrest OHCA - Ria Anggara Hamba; Candra Kusuma Negara; abd basid (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2020)
Introductin: Out-of-hospital cardiac arrest (OHCA) is the focus of global health problems due to its very high mortality rate. The reason is the late reporting and administration of CPR (Cardio Pulmonary Resuscitation) actions. A solution is to provide CPR training in the community to form a CPR bystander who can be willing to voluntarily provide CPR actions. The purpose of this study is to analyze the effect of the Subject Matter Analysis (SMA) training model on knowledge in dealing with Out-of-hospital cardiac arrest (OHCA) events. Methods: This study uses a Pre-experimental (One Group Pretest-Posttest) design using inclusion criteria. The independent variable in this study is SMA, while the dependent variable is the level of knowledge. The number of samples in this study was 50s, one group without control group. The instrument used a knowledge level questionnaire. Measuring the BLS (Basic Life Support) recognition rate was by using a questionnaire; the data were analyzed using the SPSS for Window program with a dependent t-test. Results: Based on what respondents answers there was a significant influence with the calculation of results showing ρ value = 0.001 less than 0.05. Conclusion: This means that, after the posttest, there was an increase in the level of knowledge facing the OHCA event.